Identification and validation of a locus for wheat maximum root length independent of parental reproductive environment - Chen, Huangxin; Zhao, Conghao; Yang, Yaoyao; Zeng, Zhaoyong; Li, Wei; Liu, Yanlin; Tang, Huaping; Xu, Qiang; Deng, Mei; Jiang, Qiantao; Chen, Guoyue; Peng, Yuanying; et al. (Frontiers in Plant Science, 2022)
Maximum root length (MRL) plays an important role in the uptake of nutrients and resisting abiotic stresses. Understanding the genetic mechanism of root development is of great significance for genetic improvement of wheat. Previous studies have confirmed that parental reproductive environment (PRE) has a significant impact on growth and development of the next generation in the whole life cycle of a given plant. In this study, a recombinant inbred line population genotyped using the Wheat55K SNP array, was used to map quantitative trait loci (QTL) for wheat seedling MRL based on the harvested seeds from five different PREs. A total of 5 QTL located on chromosomes 3D and 7A were identified. Among them, QMrl.sicau-2SY-3D.2 located in a 4.0 cM interval on chromosome 3D was likely independent of PREs. QMrl.sicau-2SY-7A.2 was detected in two tests and probably influenced by PREs. The effect of QMrl.sicau-2SY-3D.2 was further validated using the tightly linked kompetitive allele specific PCR (KASP) marker, KASP-AX-111589572, in populations with different genetic backgrounds. Lines with a combination of positive alleles from QMrl.sicau-2SY-3D.2 and QMrl.sicau-2SY-7A.2 have significantly longer MRL. Furthermore, four genes (TraesCS3D03G0612000, TraesCS3D03G0608400, TraesCS3D03G0613600 and TraesCS3D03G0602400) mainly expressed in wheat root were predicted to be associated with root growth. Taken together, this study reports on a major QTL independent of PREs and lays a foundation for understanding the regulation mechanism of wheat MRL at the seedling stage.